2015
DOI: 10.1186/s12871-016-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pneumoperitoneum on the cross-sectional areas of internal jugular vein and subclavian vein in laparoscopic cholecystectomy operation

Abstract: BackgroundIncreased central venous pressure secondary to an increase in intraabdominal pressure has been reported during laparoscopic surgery. However, no study has yet determined the effect of pneumoperitoneum on cross-sectional area (CSA) of central veins by ultrasonography during laparoscopic cholecystectomy. Herein, we aimed to quantify changes in CSAs of internal jugular (IJV) and subclavian veins (SCV) by ultrasonography during this surgery.MethodsThis study included 60 ASA I-II patients scheduled for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Pinar HU et al , found an increase in CSA of IJV and SCV with pneumoperitoneum of 12 mmHg at both expiration and inspiration, which decreased to prior values on desufflation. [ 7 ] This was similar to the findings of the current study, however, different pressures of pneumoperitoneum were not used in their study. Low pressure pneumoperitoneum decreases postoperative pain, analgesic consumption and seems to improve perioperative functioning of the liver and kidney.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Pinar HU et al , found an increase in CSA of IJV and SCV with pneumoperitoneum of 12 mmHg at both expiration and inspiration, which decreased to prior values on desufflation. [ 7 ] This was similar to the findings of the current study, however, different pressures of pneumoperitoneum were not used in their study. Low pressure pneumoperitoneum decreases postoperative pain, analgesic consumption and seems to improve perioperative functioning of the liver and kidney.…”
Section: Discussionsupporting
confidence: 87%
“…The duration of surgery was recorded. Pinar HU et al ,[ 7 ] in their study observed a 20% increase in IJV CSA as significant. We considered a 30% increase in CSA of IJV as significant and with a standard deviation of 0.622, to achieve a confidence level of 95% and power of 80% had to enrol 68 patients in each group.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Sustained PAP usage is linked to an increased likelihood of hypotensive events. [18][19][20][21] Limitations of the study…”
Section: Discussionmentioning
confidence: 99%